2017
DOI: 10.1177/1040638717690187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of bovine viral diarrhea virus in cattle from Mexico

Abstract: Bovine viral diarrhea virus (BVDV) infects cattle populations worldwide, causing significant economic losses though its impact on animal health. Previous studies have reported the prevalence of BVDV species and subgenotypes in cattle from the United States and Canada. We investigated the genetic diversity of BVDV strains detected in bovine serum samples from 6 different Mexican regions. Sixty-two BVDV isolates from Mexico were genetically typed based on comparison of sequences from the 5' untranslated region (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
4
13
0
2
Order By: Relevance
“…The detection results of 308 feces samples demonstrated the Taqman duplex qPCR established in this study has more simple and fast, higher sensitivity and specificity than the universal PCR. These results are consistent with a previous study [12].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The detection results of 308 feces samples demonstrated the Taqman duplex qPCR established in this study has more simple and fast, higher sensitivity and specificity than the universal PCR. These results are consistent with a previous study [12].…”
Section: Discussionsupporting
confidence: 94%
“…BVDV, belonging to Pestivirus genus in Flaviviridae, possesses a single-stranded RNA, and is classified into BVDV-1 and BVDV-2 genotypes according to the 5′ UTR sequence [10,12]. Up to date, at least 21 genetic groups of BVDV-1 and four groups of BVDV-2 have been found [1,22].…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available regarding the genetic diversity of BVDV in cattle populations from Mexico. A recent study examining viruses found in cattle from six Mexican states detected four subgenotypes: BVDV-1a, 1b, 1c, BVDV-2a, and no evidence of HoBi-like viruses were reported (19). In this study, BVDV-1c was the most frequently detected subgenotype followed by 1b, 1a, and 2a, representing a unique prevalence pattern of BVDV subgenotypes reported in North America.…”
Section: Bvdv Seroprevalence and Genetic Diversitysupporting
confidence: 42%
“…In addition, to date, HoBi-like viruses have only been detected in South America, Europe, and Asia but not in North America (16)(17)(18). Studies based on viruses found in Mexican cattle revealed the presence of at least four BVDV subgenotypes (BVDV 1a, 1b,1c, and BVDV 2a) with no evidence of HoBi-like viruses detected (19). Seroprevalence studies indicate an BVDV exposure since 1975 to date (20).…”
Section: Distribution Of Bvdv Subgenotypesmentioning
confidence: 99%
“…Additionally, the testing of FBS lots originated and packed in the US producing plants supported that the US remained free of HoBiPev (32). Similarly, extensive characterization of pestiviruses in Mexico failed to identify HoBiPev (33,34).…”
Section: Geographic Distribution Of Hobipevmentioning
confidence: 99%